Microscopic methods in analysis of submicron phospholipid dispersions - Płaczek Marcin; Kosela Magdalena (Acta Pharmaceutica)
Microscopy belongs to the group of tests, used in pharmaceutical technology, that despite the lapse of time and the development of new analytical methods, still remain irreplaceable for the characterization of dispersed drug dosage forms (e.g., suspensions and emulsions). To obtain complete description of a specific drug formulation, such as parenteral colloidal products, a combination of different microscopic techniques is sometimes required. Electron microscopy methods are the most useful ones; however, even such basic methods as optical microscopy may be helpful for determination of some properties of a sample. The publication explicates the most popular microscopical techniques used nowadays for characterization of the morphology of nanoparticles suspended in pharmaceutical formulations; ad vantages and disadvantages of these methods are also discussed. Parenteral submicron formulations containing lecithin or a particular phospholipid were chosen as examples.